2000
DOI: 10.1161/01.hyp.36.1.83
|View full text |Cite
|
Sign up to set email alerts
|

Adrenomedullin and Nitric Oxide Inhibit Human Endothelial Cell Apoptosis via a Cyclic GMP-Independent Mechanism

Abstract: Abstract-Adrenomedullin, which was discovered as a vasodilating peptide, has been reported to be produced in various organs, in which adrenomedullin regulates not only vascular tone but also cell proliferation and differentiation in an autocrine/paracrine manner. We evaluated the effect of adrenomedullin on endothelial cell apoptosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
75
0
1

Year Published

2002
2002
2009
2009

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 127 publications
(79 citation statements)
references
References 57 publications
3
75
0
1
Order By: Relevance
“…Such a result has been demonstrated in breast cancer [16], endometrial cancer [17], and endothelial [18] cells. Culture of cells under stressful conditions, such as exposure to TNFa [19], hypoxia [17] or serum deprivation [20,18] stimulates AM expression. Since our previous publications showed that AM causes cell cycle arrest and subsequent cell growth inhibition in PC-3 and LNCaP cells, we hypothesized in the present study that AM would favor cells to undergo induced-apoptosis.…”
Section: Introductionmentioning
confidence: 62%
See 2 more Smart Citations
“…Such a result has been demonstrated in breast cancer [16], endometrial cancer [17], and endothelial [18] cells. Culture of cells under stressful conditions, such as exposure to TNFa [19], hypoxia [17] or serum deprivation [20,18] stimulates AM expression. Since our previous publications showed that AM causes cell cycle arrest and subsequent cell growth inhibition in PC-3 and LNCaP cells, we hypothesized in the present study that AM would favor cells to undergo induced-apoptosis.…”
Section: Introductionmentioning
confidence: 62%
“…Resistance to apoptosis is related in these cells to a decrease in the pro-apoptotic molecules Bax and BID, and several caspases [29]. AM exerts an anti-apoptotic effect on endothelial cells cultured in serum-free conditions [18]. Such an effect occurs via cGMP-and Bcl-independent mechanisms [18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been reported that under ischemic conditions endothelial cells undergo apoptosis, but the administration of statins may prevent the decrease of existing capillary vessels resulting from ischemia. 19 Sata et al 20 reported that they administered Ach into the aorta of mice and measured the NO production as an index of relaxation response of the medial smooth muscle. After a 3-day administration of statins, the dilator response of blood vessels was significantly larger than that in the control group.…”
Section: Discussionmentioning
confidence: 99%
“…As we have previously shown that nitric oxide has an anti-apoptotic effect in endothelial cells, 22 we used the WST-1 assay to investigate whether the nitric oxide synthase inhibitor L-NAME could inhibit the anti-apoptotic cell survival effect of NcaAMPK. Although we used L-NAME concentrations from 1.0 to 5.0 mmol l À1 , L-NAME pretreatment did not inhibit cell survival (Figure 4c).…”
Section: Ampk Inhibits Anoxia-induced Apoptosis Of Huvecs D Nagata Et Almentioning
confidence: 99%